Two-step growth of κ-Ga2O3 thin films on 4H-SiC substrates with temperature-varied buffer layers using mist chemical vapor deposition. (1st January 2023) - Cho, Seong-Ho; Shin, Yun-Ji; Jeong, Seong-Min; Kwon, Se-Hun; Bae, Si-Young
Abstract: Two-step growth of κ -Ga2 O3 thin films on 4H-SiC substrates was attempted with temperature-varied buffer layers via mist chemical vapor deposition. The first-step Ga2 O3 buffer layers affect the phase formation and grain size variation depending on growth temperatures. In the second-step thin-film growth, the κ -Ga2 O3 thin film was grown at a fixed temperature of 500 °C regardless of various buffer layers. Three zones, namely, amorphous, κ phase, and mixed phase, were categorized in the κ -Ga2 O3 thin films according to the buffer growth temperature. High-quality and smooth κ -Ga2 O3 thin films could be achieved through the grain growth competition and slight buffer temperature variation in the two-step growth.